Routledge handbook of South Asian religions - Jacobsen, Knut A. 1956- (London New York, NY Routledge, 2021)
Historical South Asian religions : formative developments. The Veda / Carlos A. Lopez -- Contemporary South Asian religions : religious pluralism. Dalits and religion : anti-caste movements in India / Debi Chatterjee -- Indian religions in the U.S. / Prema Kurien.
Keywords: Electronic books; SOCIAL SCIENCE / Ethnic Studies / General; South Asia -- Religion; South Asia; Electronic books